Resilience engineering: Current status of the research and future challenges - Patriarca, Riccardo; Bergström, Johan; Di Gravio, Giulio; Costantino, Francesco (Safety science, 2018)
•We present a methodology based on Factor Analysis and MDS for literature reviews.•We introduce the notion of research factor related to the presented methodology.•We summarize the state of the art about RE through 5 research factors.•We suggest future multi-disciplinary research directions for RE. This paper offers an extensive literature review on the field of Resilience Engineering (RE), encompassing 472 contributions, including journal articles, conference proceedings and book chapters. Adopting the numbers of co-citations as a metric of conceptual proximity, this paper details the application of Factor Analysis and Multi-Dimensional Scaling, as groundbreaking means to extract relevant research factors. A temporal analysis in a multi-variate two-dimensional space confirms the significance and relevance of the identified research factors. An in-depth analysis of the five research factors, labeled as the need of RE, RE for modelling, defining and exploring RE, reflecting on RE, RE and improvisation, guides the definition of future research paths and open research questions within the field and across several domains, suggesting the need for multi-disciplinary future studies.